Neonatal seizures in the U.S. National Inpatient Population: Prevalence and outcomes - Swetha Padiyar; Leen Nusairat; Amer Kadri; Jalal Abu-Shaweesh; Hany Aly (Pediatrics and Neonatology)
Background: Seizures are the most frequent neurological manifestation in neonates. Prevalence of neonatal seizures has not been well described in relationship with gestational age (GA). Also, the impact of seizures on neonatal mortality has not been quantified. This study aims to determine 1) prevalence of neonatal seizures in all GA groups, 2) associated mortality in each GA group and 3) impact of seizures on length of stay (LOS) of survivors in each GA group. Methods: Data from the national Kids' Inpatient Database (KID) for the years 2006, 2009 and 2012 was used in the study. All admitted infants with a documented GA were included in the study. All categorical variables were analyzed using Chi-square test, continuous variables were analyzed using t-test, and logistic regression analysis used to calculate odds ratio (OR) and 95% confidence intervals (CI). Results: A total of 10, 572,209 infants were included, of whom 4400 infants (0.04%) had seizures. The highest prevalence was at 24 weeks (0.12%). Overall mortality rate of patients with seizures was 4% with OR = 2.24 (95% CI = 1.90–2.65, p < 0.001). The correlation of seizure with mortality was significant after 33 weeks GA with greatest impact at 33–36 weeks GA (OR = 46.38 (95% CI = 26.86–80.08, p < 0.001). Seizures were associated with increased median LOS from 2 to 4 days (p < 0.001). Conclusion: The prevalence of seizures varies according to gestational age ranging from 0.02% to 0.12%. The highest prevalence is at 24 weeks GA. The greatest impact for seizures on mortality is at 33–36 weeks GA.